Avaliação do estado nutricional de crianças com disfagia por paralisia cerebral - Linhares, Francisca Márcia Pereira (2004)
The objective of this study was to evaluate the nutritional conditions of children with dysphagy caused by brain paralysis to investigate if the phonoaudiologic treatment has had any kind of influence in their nutritional conditions. These children are being taken care by a multidisciplinary staff at Antonio Francisco Lisboa School in the city of Santa Maria, RS. It was criteria to evaluate the children's nutritional state, an anthropometric test was utlized considering the variables height and age expressed in Z-score for a standard deviation of -2, which is the criteria utlized by the National Center for Health Statistics (NCHS 1986) as a comparison measure. Other variables such as socio-economic level, clinical exam and nutritious inquiry were also investigated to complement the evaluation of the nutritional conditions. The study consisted of 20 subjects with dysphagy caused by brain paralysis withages ranging from 1 to 10 years old, belonging to both sexes. The results have demonstrated that the group with dysphagy caused by brain paralysis, considering the anthropometric test, has presented a prevalence of 45% of height deficit for the age, while the control group has not presented height deficit for the age. Was concluded that in the anthropometric test the subjects with dysphagy have high prevalence of underfeeding (height deficit for the age) if compared to the international reference pattern and that this high prevalence might be related to dyspahgy. Other aspects such as the low socio- economic level of the families and low calory ingestion may have contributed to worsen the nutritional conditions of the children with dysphagy. Was observed that the subjects who are undertaking a phonotherapic treatment have presented a better nutritional state.